Incidence of Tuberculosis Among Young Children in Rural Mozambique. Issue 7 (July 2015) - López-Varela, Elisa; Augusto, Orvalho Joaquim; Gondo, Kizito; García-Basteiro, Alberto L.; Fraile, Oscar; Ira, Tasmiya; Ribó Aristizabal, Jose Luis; Bulo, Helder; Muñoz Gutierrez, José; Aponte, John; Macete, Eusebio; Sacarlal, Jahit; et al.
Abstract : Background: Tuberculosis (TB) contributes significantly to child morbidity and mortality. This study aimed to estimate the minimum community-based incidence rate of TB among children <3 years of age in Southern Mozambique. Methods: Between October 2011 and October 2012, in the Manhiça District Health and Demographic Surveillance System, we enrolled prospectively all presumptive TB cases younger than 3 years of age through passive and active case finding. Participants included all children who were either symptomatic or were close contacts of a notified adult smear-positive pulmonary TB. Children were clinically evaluated at baseline and follow-up visits. Investigation for TB disease included chest radiography, HIV and tuberculin skin testing as well as gastric aspirate and induced sputum sampling, which were processed for smear, culture and mycobacterial molecular identification. Results: During the study period, 13, 764 children <3 years contributed to a total of 9575 person-year. Out of the 789 presumptive TB cases enrolled, 13 had TB culture confirmation and 32 were probable TB cases. The minimum community-based incidence rate of TB (confirmed plus probable cases) was 470 of 100, 000 person-year (95% confidence interval: 343–629 of 100, 000). HIV co-infection was present in 44% of the TB cases. Conclusion: These data highlight the huge burden of pediatric TB. This study provides one of the first prospective population-based incidence data of childhood tuberculosis and adds valuable information to the global effort of producing better estimates, a critical step to inform public health policy. Abstract : Supplemental Digital Content is available in the text.